COMPUTERIZED VERSUS TRADITIONAL TECHNIQUES OF ANESTHESIA USED IN ORAL SURGERY - Emilia Bologa; Ovidiu Ștefănescu; Cristina Popa; Alexandra Platon; Carmen Gabriela Stelea (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study This review focuses on Computer-Controlled Local Anaesthetic Delivery systems (CCLAD) versus conventional carpule anaesthesia in its efficiency to reduce pain and anxiety. Material and methods For this purpose, we have searched for relevant studies in Science Direct, Thomson ISI - Web of Science, Scopus, PubMed, Google Scholar covering the period up to December 2018. We have included only the studies investigating oral surgery maneuvers that compared clinically CCLAD to conventional techniques. The authors looked mainly for data on pain, anxiety and effectiveness related to anaesthesia. Results The review provides a critical overview of 6 studies (n=325 subjects). Conclusions The review enabled the authors to draw the conclusion that CCLAD results in significantly lower level of pain perception compared to conventional injections, and it is a promising device for helping patients deal with pain perception. The literature needs to be expanded, mostly regarding anxiety and efficiency in oral surgery.